Serum and Cerebrospinal Fluid Lactate Dehydrogenase in Children with Febrile Convulsions - bidabadi, Elham; Ahmadi Aliabadi, Leila; Khosousi, Mohammad-Javad; Mashouf, Parham; Shahraki, Tamkin; Tohidi, Sepehr; Hasandokht, Tolou (Iranian Journal of Child Neurology, 2023)
Objective Tissue damage caused by febrile convulsion has not still been proved or refuted completely. Given the fact that lactate dehydrogenase as an intracellular enzyme can be increased due to tissue damage, we decided to evaluate serum and cerebrospinal fluid lactate dehydrogenase in children with febrile convulsion. Materials & Methods This is a cross-sectional study on 166 children aged 6-24 month, in three groups of simple febrile convulsion (n=56), complex febrile convulsion (n=27) with 3 different subgroups (recurrence in 24 hours, duration >15 minutes, and with focal components), and control (n=83). Patients’ serum and cerebrospinal fluid specimens were collected after meeting the inclusion criteria. Demographic information was documented and patients’ serum and cerebrospinal fluid lactate dehydrogenase and glucose were measured. Data were analyzed using SPSS software. Result The mean serum lactate dehydrogenase in simple febrile convulsion, complex febrile convulsion, and controls were 501.57± 143.70, 553.07±160.22, and 505.87±98.73 U/L, respectively. The mean cerebrospinal fluid lactate dehydrogenase in simple, complex febrile convulsion, and control groups were 22.58±11.92, 29.48±18.18, and 21.56±17.32 U/L, respectively. Only cerebrospinal fluid lactate dehydrogenase difference between complex febrile convulsion and control group (p=0.039) (In the duration >15 minutes subgroup and controls, p=0.028) was statisticallysignificant. There was a significantThere was a significant difference between sex and serum lactate dehydrogenase in the same subgroup of complex group (p=0.012). Conclusion Complex febrile convulsion may lead to increase of lactate dehydrogenase in cns of CNS cellular damage